Displasia cemento-óssea: 5 anos de registros imaginológicos - Silva, Laura Garcia [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Bone dysplasia is a benign fibro-osseous lesion and is commonly found in clinical practice, there is a predilection for females and approximately 70% of cases affect blacks, characterized by the development of fibrous tissue and immature, lamellar bone and cement-like particles which gradually replace the normal bone.Radiographically it presents as an initial radiolucent area and subsequent radiopaque foci. It can be focal, periapical and florid according to the anatomical areas involved and radiographic features. The main differential diagnoses of bone dysplasia include ossifying fibroma, fibrous dysplasia, and cementoblastoma. A 42-year-old female patient, leucoderma searched dental treatment at a private clinic for implants to replace missing teeth. At the end of 2015, a tomographic examination was requested for bone analysis and conclusion of the case in question. The result of the CT scan revealed a radiopaque lesion circumscribed with radiolucent halo at the apex of the tooth 23, with pulp vitality, without painful thickening of the lamina. The professional inspected the patient documentation file and found periodic panoramic radiographs performed by the patient, dating to 2010, 2011, 2013 and 2015. In analyzing them it is noted that the lesion established at the apex of the tooth 23 was found from the first radiography performed as a discrete radiolucent area and over the years note the appearance of radiopaque areas and a discrete increase in size. The radiographic documentation of the patient is very important for the diagnosis of oral pathologies, especially the bone cement dysplasia, since the patient does not present any clinical manifestation or pain in the region where the lesion is developing. The professional should...

A displasia óssea é uma lesão fibro-óssea de caráter benigno e é comumente encontrada na prática clínica. Há predileção por mulheres e aproximadamente 70% dos casos afeta negros. Caracterizada pelo desenvolvimento de tecido fibroso e osso imaturo, lamelar e partículas semelhantes ao cemento que substituem gradualmente o osso normal. Radiograficamente se apresenta como uma área radiolúcida na lesão inicial e conteúdo radiopaco no estágio final. Pode ser classificada em focal, periapical e florida de acordo com as áreas anatômicas envolvidas e características radiográficas. Os principais diagnósticos diferenciais da displasia óssea incluem o fibroma ossificante, odontoma, osteoblastoma e osteomielite esclerosante crônica. Este trabalho relatou um caso clínico com diagnóstico de displasia cemento-óssea periapical, efetuado 5 anos após o primeiro registro imaginológico. Paciente do sexo feminino, 42 anos, leucoderma, procurou atendimento odontológico em uma clínica particular para reabilitação oral com instalação de implantes dentários. Ao final da instalação dos implantes, no ano de 2015, foi solicitado exame tomográfico por feixe cônico para análise da inserção óssea e conclusão do caso. Na análise das imagens tomográficas, notou-se uma lesão hiperdensa circunscrita com halo hipodenso no ápice do dente 23, sem espessamento da lâmina dura. Ao exame clínico, o dente 23 apresentou vitalidade pulpar. Ao analisar o arquivo de documentação da paciente, foram localizadas radiografias panorâmicas periódicas realizadas nos anos de 2010, 2011, 2013 e 2014. Ao analisá-las, verificou-se que a lesão estabelecida no ápice do dente 23 foi identificada, desde a primeira radiografia realizada, como uma área radiolúcida discreta, e com o passar dos anos, houve o aparecimento de áreas radiopacas no interior da lesão e um discreto...
Keywords: Doenças do desenvolvimento ósseo; Diagnóstico bucal; Tomografia Computadorizada de Feixe Cônico; Bone Diseases, Developmental